Transoral robotic tongue base reduction and supraglottoplasty combined with maxillomandibular advancement: a new option for selected sleep apnea patients? Preliminary report - Dallan, Iacopo; Cristofani-Mencacci, Lodovica; Seccia, Veronica; Cambi, Christina; Fiacchini, Giacomo; Berrettini, Stefano; Brevi, Bruno (European archives of oto-rhino-laryngology, 2019)
Purpose Transoral robotic surgery (TORS) and maxillo-mandibular advancement (MMA) are effective options for obstructive sleep apnea patients. Identification of the correct candidate is by far the most important item in achieving a succesful outcome. As a consequence, not all patients can be managed successfully via one or the other procedure. To overcome the limits of any single procedure we have combined, in a very selected population of patients, TORS tongue base reduction and MMA. Preliminary data are encouraging, in terms of both AHI and ESS. Methods A retrospective cohort study was conducted on five patients treated with combined TORS-MMA surgery. Demographic and clinical data, pre-operative and post-operative PSG and ESS were collected. Results Three of five patients were recruited. All patients presented severe OSAHS. Mean AHI and ESS went respectively from 48 and 12 pre-operatively to 19 and 4 post-operatively. Minor bleeding occurred in two patients. No significant sequelae have been reported. Conclusions Combined TORS and MMA is feasible and safe. Our very preliminary data are encouraging, in terms of both AHI and ESS. Long-term follow-up and a larger amount of subjects are needed to confirm this surgical approach as a valuable option for selected OSAHS patient.